2018
DOI: 10.1007/s11845-018-1831-0
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac screening in a high-risk population: paediatric type 1 diabetes—a review of current guidelines and practice

Abstract: Timely diagnosis of CD can prevent chronic ill health in affected individuals, and in patients with T1DM, CD is an independent risk factor for increased morbidity and mortality. Given the high prevalence of atypical symptoms and silent CD in those with T1DM, in this and other studies, and the benefits of detection and treatment of CD, screening is essential. Large-scale data collection allowing for the development of evidence-based guidelines is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In our study, CD was diagnosed in 7% of the patients with T1DM. This frequency is similar to the rates reported in previous studies (3,(5)(6)(7)(12)(13)(14). CD is diagnosed in patients at the time of T1DM diagnosis and usually within the first 5 years of follow-up (7,14,15).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, CD was diagnosed in 7% of the patients with T1DM. This frequency is similar to the rates reported in previous studies (3,(5)(6)(7)(12)(13)(14). CD is diagnosed in patients at the time of T1DM diagnosis and usually within the first 5 years of follow-up (7,14,15).…”
Section: Discussionsupporting
confidence: 89%
“…The co-occurrence of T1DM and CD may result in inadequate blood sugar regulation, poor metabolic control, frequent hypoglycemia attacks, short stature, delayed puberty, vitamin and mineral insufficiency, and a decrease in bone mineral density (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, extra-intestinal manifestations (short stature, iron deficiency anemia, or delayed puberty) and silent forms are more frequent. Recently published studies have shown that up to 71.4% of children with T1DM do not have gastrointestinal symptoms when CD-specific antibodies are detected [ 41 , 42 ]. International guidelines recommend CD screening at T1DM diagnosis and annually for five years [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The close association between CD and T1DM has been known for more than 50 years, and, generally, this marked tendency has led to two manifestations found to co-occur in 5-15% of CD patients [40]. This relationship may be because both diseases partially share the same genetic basis, and the DQ2/DR3 haplotypes are frequently present in the CD/T1DM patients [41], although both diseases are polygenic and have a greater susceptibility in several common loci, distributed over different chromosomes.…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 99%